Interleukin-6 (IL-6) Level as an Indikator of Progresivity Rheumatoid Arthritis (RA) Disease - Putu Oky Ari Tania; Dorta Simamora; Wahyuni Dyah Parmasari; Febtarini Rahmawati (Universitas Wijaya Kusuma Surabaya, 2014)
Rheumatoid Arthritis (RA) is autoimmune disease that attacks joints and synovial tissues. Rheumatoid Arthritis is characterized by inflammation that involves production of cytokines such as Interleukin 6 (IL-6). Increasing of interleukin 6 has correlation with activity and progressivity of the disease. This research was designed to know whether IL- 6 could be used as indicator progressivity of RA. The method that used for measuring IL-6 level is ELISA (Enzyme Linked Immunosorbent Assay), using the principle antigen-antibody binding. In early stage there were 9 persons (S01, S02, S03, S04, S07, S08, S09, S10 and S14) with of IL-6 level (mean : 3.640 pg/mL), intermediate stage there were 3 persons (S06, S13 and S15) with IL-6 level (mean : 12.453 pg/mL), late stage : 3 persons (S05, S11 and S12) with IL-6 level (mean : 59.349 pg/mL).